Association between remote diffusion‐weighted imaging lesions and cerebral small vessel disease in primary intracerebral hemorrhage. (5th March 2019) - Xu, X.‐h.; Ye, X.‐h.; Li, J.‐w.; Cai, J.‐s.; Gao, T.; Zhang, W.‐j.; Zhao, G.‐h.; Tong, L.‐s.; Gao, F.
Abstract : Background and purpose: The aim of this study was to examine the association amongst remote diffusion‐weighted imaging lesions (R‐DWILs), imaging markers of cerebral small vessel disease (cSVD) and total cSVD burden in patients with primary intracerebral haemorrhage (ICH). Methods: In total, 344 consecutive primary ICH patients were enrolled prospectively. R‐DWILs on magnetic resonance imaging as well as four imaging markers of cSVD, including cerebral microbleeds (CMBs), white matter hyperintensities (WMHs), lacunes and enlarged perivascular spaces, were rated with validated scales. The total cSVD score was calculated by adding up these four markers. Univariate and multivariate analyses were performed. Results: Remote DWI lesions were detected in 57 (16.6%) primary ICH patients. On multivariate logistic regression analysis, the presence of CMBs [odds ratio (OR) 5.26, 95% confidence interval (CI) 1.72–16.12], of high‐grade WMHs (OR 4.68, 95% CI 2.01–10.90), the presence of lacunes (OR 2.69, 95% CI 1.20–6.06), mixed CMBs (OR 2.93, 95% CI 1.35–6.36), mixed lacunes (OR 3.60, 95% CI 1.25–10.37), periventricular WMHs (OR 2.19, 95% CI 1.40–3.44), deep WMHs (OR 1.92, 95% CI 1.24–2.97) and total WMHs (OR 1.52, 95% CI 1.20–1.94) were associated with the presence of R‐DWILs. A significant association was also found between high‐grade total cSVD score and R‐DWILs (OR 1.97, 95% CI 1.36–2.84). This association remained significant in patients stratified by an age of 60 years or more than 60 years. Conclusions: Remote DWI lesions are correlated with the severity of each imaging marker of cSVD and with the total burden of cSVD.